Physicians' perception about predictors of opioid abuse in patients with chronic non-cancer pain: a Delphi study - Galán, Santiago; de la Vega, Rocío; Esteve, Rosa; López-Martínez, Alicia E.; Fernández Baena, Mariano; Ramírez-Maestre, Carmen (Frontiers in Pain Research, 2023)
Background Opioids are being prescribed widely, and increasingly, for the treatment of chronic non-cancer pain (CNCP). However, several side effects are associated with mid- and long-term opioid use and, for certain patients, with the risk of problematic opioid use. The aim of this study is to know the perception of the physicians about which variables could be associated with increased risk of patients with CNCP developing a problem of abuse or misuse of the prescribed opioid medication. Methods Twenty-nine physicians with experience in CNCP pain management and opioids prescription participated in a two-round Delphi study focused on the risk factors for opioid misuse and abuse. Results The variables that reached consensus regarding their relationship with the increased risk of suffering a problem of opioid abuse or misuse were: (1) Experiencing pain on a daily basis, (2) previous use of high-dose opioids, (3) generalized anxiety, (4) hopelessness, (5) benzodiazepine intake, (6) use of opioids for reasons other than pain, (7) family problems, family instability or family breakdown, and (8) having access to several opioid prescribers. The only variable that reached consensus regarding it not being associated to a possible risk of abuse or misuse was having mild pain intensity (0–4 on a NRS-11). Conclusions This study provides useful information that could help make decisions about the use of opioids for CNCP treatment and prevent future difficulties. Prospective studies testing the relationship of the variables that reached consensus with the risk of opioid misuse and abuse are warranted. Significance This study shows the variables of CNCP that the professional must take into account in order to avoid possible problems when prescribing opioids.